Potential use of serum‐derived bovine immunoglobulin/protein isolate for the management of COVID‐19. Issue 7 (10th June 2021) - Utay, Netanya S.; Asmuth, David M.; Gharakhanian, Shahin; Contreras, Moises; Warner, Christopher D.; Detzel, Christopher J.
Abstract: COVID‐19 manifests as a mild disease in most people but can progress to severe disease in nearly 20% of individuals. Disease progression is likely driven by a cytokine storm, either directly stimulated by SARS‐CoV‐2 or by increased systemic inflammation in which the gut might play an integral role. SARS‐CoV‐2 replication in the gut may cause increased intestinal permeability, alterations to the fecal microbiome, and increased inflammatory cytokines. Each effect may lead to increased systemic inflammation and the transport of cytokines and inflammatory antigens from the gut to the lung. Few interventions are being studied to treat people with mild disease and prevent the cytokine storm. Serumderived bovine immunoglobulin/protein isolate (SBI) may prevent progression by (1) binding and neutralizing inflammatory antigens, (2) decreasing gut permeability, (3) interfering with ACE2 binding by viral proteins, and (4) improving the fecal microbiome. SBI is therefore a promising intervention to prevent disease progression in COVID‐19 patients.